Strike of Spanish Iron Ore Seamen : inter-departmental correspondence - Carthy, A. E.
001-0203-001 TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE From. A.E.Carthy Department. International. To. Sir. WALTER CITRINE Date June10, 1936, SUBJECT. STRIKE OF SPANISH IRON ORE SEAMEN. No precise information is available about the situation in Aberdeen, but the following is a resume of recent history in the Spanish mercantile marine. A strike of seamen in all the ports of Spain began on May 1 last and was settled on May 5 following grant of increased wages. Round about May 20, upon the arrival in British ports of certain Spanish iron ore steamers, a strike broke out on four of them at Workington; another vessel which arrived later joined them. The demands were: 100 per cent, increased wages, 20 days' annual holiday with pay, further reduction of working hours, increase of crews by two firemen, running of vessels on Communistic lines, with a commission of seamen's representatives in full charge. On May 20 there were 54 Spanish steamers in English ports. The strike spread to Newcastle, Hull, Middlesbrough, Cardiff and Aberdeen, and 12 ships and 350 men were involved. The Workington dock was blocked by the dispute, and on June 7 the 5 steamers were boarded by the police, after consultations between the Spanish Consul and his Ambassador, and one was taken outside the three-mile limit by a local crew, which returned with the police. The Spanish Government was said to have been willing to pay the men 100% increased wages if they would call off the strike, and they lose this by having declined. It is not clear exactly what the Government's offer, or the men's claim, for wages, involves, but from a statement that the Spanish Government would reimburse the Workington Dock and Harbour Board if they advanced the 100 per cent. increased wages to the crews in Workington, wage rates for handling cargo may be alone involved. In Cardiff, the Trades and Labour Council gave sympathetic support to the strikers in Cardiff Dock, where the demands were 90% increased wages and 40-hour week. Concessions were made by the shipowners which were inacceptable to the men. AEC/873 292/946/1/203